Freedom of the Seas and US Foreign Policy : An Intellectual History - Donahue, Connor (Corbett centre for maritime policy studies series, 2024)
"This book critically analyzes US political-military strategy by arguing that freedom of the seas discourse is fundamentally unfit for an era of maritime great power competition. The work conducts a genealogical intellectual history of freedom of the seas discourse in U.S. foreign policy to show how the concept has evolved over time to facilitate American control over the global ocean space. It concludes that the contemporary discourse works to establish the high seas as an arena free from claims of sovereignty so that the United States, as the presumed unrivaled naval power, can intervene globally on behalf of its national interests. However, since sea control strategies depend on a preponderance of material force, as the U.S. wanes in relative material capability it becomes less able to support political-military strategies predicated on the assumption of global naval dominance. The book provides a timely commentary on the current geopolitical competition between the United States and China, and critiques the US approach towards China in the maritime domain in order to highlight potential avenues of foreign policy action that may enable the two countries to mitigate the risk of conflict. This book will be of much interest to students of naval history, maritime security, US foreign policy and International Relations"--